Links of non-free mechanical man-made systems - P. D. Balakin (Омский научный вестник: Серия "Авиационно-ракетное и энергетическое машиностроение")
The paper gives a complete classification of the links of non-free mechanical technogenic systems. It is shown that the joint use of holonomic and non-holonomic constraints in mechanical systems allows the creation of systems with adaptive properties. The main method of synthesis of such systems is an additional motion to the main motion of the links, which can be either a small motion of self-adjustment or elastic deformation, or significant coming from the control circuit integrated in the system